(3ehUd GdWdGH Edi bhGYO GdEYQGHs - (3GdLQLGhj GdCRgQj GdeUQj, Rjf GdOjf, GdhbGO, NGdO Hf YHO Gddg Hf CHj HcQ, J (B905 (3g`s
(3ChdgG (B:s
(3GdMeO ddg Gdedge dMeOg hGdUdGI hGdSdGe Ydi SjOfG eMeO QShdg hYHOg hYdi Bdg hUMHg hLfOg hHYO ajbhd GdYHO GdabjQ Edi ehdGg GdZfjs
(3BNQgG (B:s
(3hGdMeO ddg aj GdeHOC hGdfgGjI hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjeG cKjQG OGFeG UdGI hSdGeG OGFejf eJdGRejf Edi jhe GdOjf hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 297s
(3eYLe GdeDdajf(B: 8 / 26s
(3cTa GdXfhf(B: 1 / 124s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs